Cognitive modalities in a course based on mobile learning - Abelardo Mancinas González (Universidad de Guadalajara, 2018)
The objective of this research was to explore the function of smartphones in the modes of cognition. The research question refers to the modes of cognition associated with the use of mobile devices in a university course. To answer this inquiry, we used an exploratory type study, with a qualitative approach and design of case study with multiple units. The sample consisted of 53 students of the degree in Engineering in Business Management of the Instituto Tecnológico de Hermosillo. To collect the data we used the semi-structured interview, the participant observation, the survey and the analysis of secondary documents. Qualitative data were analyzed using linear and axial coding. The results show the predominance of knowledge modalities such as empirical cognition and distributed cognition, which contrast with the results obtained by other studies on mobile learning and the development of cognitive skills. We conclude that mobile learning induce an empirical cognition, based on the execution of procedures that oscillate between the algorithmic and the heuristic mental activity